2020
DOI: 10.1128/aem.01163-20
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Inducible Toluene Monooxygenase That Cooxidizes 1,4-Dioxane and 1,1-Dichloroethylene in Propanotrophic Azoarcus sp. Strain DD4

Abstract: Cometabolic degradation plays a prominent role in bioremediation of commingled groundwater contamination (e.g., chlorinated solvents and the solvent stabilizer 1,4-dioxane [dioxane]). In this study, we untangled the diversity and catalytic functions of multi-component monooxygenases in Azoarcus sp. DD4, a gram-negative propanotroph that is effective in degrading dioxane and 1,1-dichloroethylene (1,1-DCE). Using a combination of knockout mutagenesis and heterologous expression, a toluene monooxygenase (MO) enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…It is important to note that the same tmo gene cluster was described in case of the propanothrophic Azoarcus sp. strain DD4, hinting at the spread of this gene cluster among toluene degraders of the Burkholderiales by horizontal gene transfer. Around 20 kilobases downstream of the gene cluster coding for Tmo, another cluster was found that coded for a multicomponent phenol hydroxylase (mPH) and a complete meta -cleavage pathway (mPH1 cluster).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the same tmo gene cluster was described in case of the propanothrophic Azoarcus sp. strain DD4, hinting at the spread of this gene cluster among toluene degraders of the Burkholderiales by horizontal gene transfer. Around 20 kilobases downstream of the gene cluster coding for Tmo, another cluster was found that coded for a multicomponent phenol hydroxylase (mPH) and a complete meta -cleavage pathway (mPH1 cluster).…”
Section: Resultsmentioning
confidence: 99%
“…Metatranscriptomic sequencing revealed that among the multiple monooxygenase genes detected in the culture, including toluene monooxygenase, 4hydroxyphenylacetate 3-monooxygenase, nitronate monooxygenase, salicylate 1-monooxygenase and alkanesulfonate monooxygenase genes, the most abundant monooxygenase genes from ZM13 were identi ed as toluene monooxygenase (Additional le 1: Table S7 and Figure S9), which belong to Group SDIMOs. A recent study rstly proved the 1,4-dioxane degradation function of toluene monooxygenase in a propanotrophic strain DD4 [41]. In addition, the network analysis demonstrated the important role of ZM13 as a bottleneck, serving as a bridge that connected different parts of the community.…”
Section: Discussionmentioning
confidence: 95%
“…In DD4, though 1-propanol can induce the expression of TMO, it is the product of the oxidation of propane by TMO, which thus doesn't compete with dioxane for the active sites of TMO. 30 Further, alcohol substrates are miscible with water and can be easily operated for field injection and monitoring. However, 1-propanol and other alcohol substrates are less selective to the inocula and thus more suited for low biomass environments dominated by oligotrophic microbiomes that respond poorly to the addition of auxiliary substrates, such as deep bedrock aquifers.…”
Section: Discussionmentioning
confidence: 99%
“…The primers and other materials used in the RT-qPCR procedures are described in our previous publication. 30 Differential gene expression was quantified using the 2 −ΔΔ C q method 32 with tmoA as the target gene and 16S rRNA as the housekeeping gene. The expression fold change was calculated with the following formula:ΔΔ C q,Targetgene = ( C q,Targetgene − C q,Housekeepinggene ) Treatment − ( C q,Targetgene − C q,Housekeepinggene ) Control …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation